Using the turtle excluder device (TED) in the pink shrimp trawling fishery off southern Brazil - Schroeder, Rafael; Bottene, Bruno R.; Sant Ana, Rodrigo; Wahrlich, Roberto; Queirolo, Dante (Latin american journal of aquatic research, 2016)
The use of the turtle excluder device (TED) has been mandatory in Brazil since 1994. In spite of the importance of sea turtle bycatch reduction, TED effectiveness to maintain target species capture had never been evaluated in shrimp fisheries off southern Brazil. F or this purpose, a test was carried out in November 2013 with the TED installed with two different configurations, top or bottom opening under the supervision of a technician of the National Oceanic and Atmospheric Administration (NOAA). Absolute catch and fishery yields were simultaneously monitored in 10 fishing hauls of a double-rig trawler by an onboard observer in one net equipped with a TED and the other without a TED. Although a Bayesian hypothesis test demonstrated no significant differences through the simultaneous comparison of absolute capture considering the use and nonuse of the TED, the credibility interval of posterior beta distributions intercepted almost its minimum limit which weakens the hypothesis of equality. In terms of orientation, the model mounted with the top opening showed no differences in absolute catches of the target species in respect to control.